WORKSHOP ROBOTIK DAN MIKROCONTROLLER PADA SISWA SMK BINA INSAN SIAK HULU - Zulafwan Zulafwan; Rahmi Mulyati; Haris Tri Saputra; Syahrul Syahrul (LPPM Universitas Bina Bangsa, 2022)
This community service activity is carried out as a form of devotion from AMIK Tri Dharma Pekanbaru lecturers to the community, as for the materials chosen in this activity are robotics and microcontrollers, the target is students majoring in computer network engineering at SMK Bina Insan Siak Hulu. The activity was carried out by explaining the theory about robotics and microcontrollers to the participants, then the presenters would practice and demonstrate about making simple robotics. This activity aims so that participants can know and be able to understand science about robotics and microcontrollers, especially in the era of the industrial revolution 4.0, knowledge about robotics and microcontrollers is needed. robotics and microcontrollers. It is hoped that the participants will continue to explore their knowledge after the activity is completed from various references on the internet